Lumbar posterior group muscle degeneration: Influencing factors of adjacent vertebral body re-fracture after percutaneous vertebroplasty - Chen, Ming; Yang, Cekai; Cai, Zhuoyan; Liu, Youtao; Liu, Hao; Cui, Jianchao; Yao, Zhensong; Chen, Yuan (Frontiers in Medicine, 2023)
Objective:To explore the influencing factors of adjacent vertebral re-fracture after percutaneous vertebroplasty(PVP)for osteoporosis vertebral compression fractures(OVCFs). Methods:We retrospectively analyzed the clinical data of 55 patients with OVCFs who underwent PVP operation in our hospital from January 2016 to June 2019 and followed up for one year，then put them in the fracture group.At the same time, the clinical data of 55 patients with OVCFs without adjacent vertebral re-fracture were collected and followed up for 1 year after PVP operation, and then they were included in the non-fracture group.We performed univariate and multivariate logistic regression analysis on the influencing factors of adjacent vertebral re-fracture in patients with OVCFs after PVP. Results:There were significant differences in body mass index(BMI), bone mineral density(BMD)T value, amount of bone cement injected, bone cement leakage, history of glucocorticoid use, cross-sectional area(CSA),Cross-sectional area asymmetry(CSAA),fat infiltration rate(FIR)and fat infiltration rate asymmetry(FIRA) of lumbar posterior group muscles (multifidus(MF) and erector spinae(ES))between the two groups(P<0.05).There was no significant difference in sex, age, time from the first fracture to operation, the CAS,CSAA,FIR and FIRA of psoas major(PS) between the two groups(P>0.05).Multivariate logistic regression showed that higher dose of bone cement, greater CSAA and FIR of multifidus, and higher CSAA of erector spinae were independent risk factors for recurrent recurrent fractures of adjacent vertebrae after PVP. Conclusions:There are many risk factors for recurrent vertebral fracture after PVP in patients with OVCFs, and degeneration of paraspinal muscles (especially posterior lumbar muscles) may be one of the risks.